Alterations in gut microbiota and metabolites contribute to postoperative sleep disturbances - Hui Zhong; Meiru Jiang; Kun Yuan; Fang Sheng; Xiuyun Xu; Yong Cui; Xijia Sun; Wenfei Tan (Animal Models and Experimental Medicine)
Abstract Background The composition of the intestinal flora and the resulting metabolites affect patients' sleep after surgery. Methods We intended to elucidate the mechanisms by which disordered intestinal flora modulate the pathophysiology of postoperative sleep disturbances in hosts. In this study, we explored the impacts of anesthesia, surgery, and postoperative sleep duration on the fecal microbiota and metabolites of individuals classified postprocedurally as poor sleepers (PS) and good sleepers (GS), as diagnosed by the bispectral index. We also performed fecal microbiota transplantation in pseudo‐germ‐free (PGF) rats and applied Western blotting, immunohistochemistry, and gut permeability analyses to identify the potential mechanism of its effect. Results Research finding shows the PS group had significantly higher postoperative stool levels of the metabolites tryptophan and kynurenine than the GS group. PGF rats that received gut microbiota from PSs exhibited less rapid eye movement (REM) sleep than those that received GS microbiota (GS‐PGF: 11.4% ± 1.6%, PS‐PGF: 4.8% ± 2.0%, p < 0.001). Measurement of 5‐hydroxytryptophan (5‐HTP) levels in the stool, serum, and prefrontal cortex (PFC) indicated that altered 5‐HTP levels, including reduced levels in the PFC, caused sleep loss in PGF rats transplanted with PS gut flora. Through the brain–gut axis, the inactivity of tryptophan hydroxylase 1 (TPH1) and TPH2 in the colon and PFC, respectively, caused a loss of REM sleep in PGF rats and decreased the 5‐HTP level in the PFC. Conclusions These findings indicate that postoperative gut dysbiosis and defective 5‐HTP metabolism may cause postoperative sleep disturbances. Clinicians and sleep researchers may gain new insights from this study.